Eupholidoptera karatolosi sp.n. and E. mirzayani sp.n. (Orthoptera, Tettigoniidae), two new bushcrickets from Greece and Iran - Mofidi-Neyestanak, Mohsen; Quicke, Donald L.j. (Zootaxa, 2007)
Eupholidoptera karatolosi Mofidi-Neyestanak & Quicke from Greece and E. mirzayani Mofidi-Neyestanak & Quicke from Iran, two new species of bushcrickets (Orthoptera, Tettigoniidae: Platycleidini), are described and distinguished from closely related species based on morphology. Species relationships within Eupholidoptera Maran are discussed and some species are given new assignments. A simplified illustrated identification key to the species of Eupholidoptera is provided to accommodate the new species. They are being described since they have been used to generate DNA sequence data that will be published elsewhere as part of a phylogenetic study of the tribe Platycleidini.